Theoretical and experimental investigation of solar heat potential at low temperatures: Towards large scale integration in the agro food sector, ISBN 1309-0127 - Boutagriout Badreddine; Chaabane Hamouda; Smadi Hacene (IJRER International Journal of Renewable Energy Research, 2016)
Several applications in the agro food sub-sector have been classified as suitable to be supplied by solar heating systems. The present work deals with the potential evaluation of solar thermal energy under climatic conditions of Algeria. In a first part, an experimental investigation conducted on small scale solar water heating system is presented followed by simulation. The experimental tests revealed the thermal behavior of the system as well as the outlet temperature levels which can be reached by locally manufactured flat plat collectors. The second part presents the potential of solar heat for industrial applications, particularly those consisting of heating make-up water and water feedback from heat recovery wich exists in almost all the agro food industries. Thus, water inlet temperature through the secondary circuit is considered to be ranging from 20 to 90°C. The results showed that the annual specific energy yield delivered by the solar system decreases by increasing water feedback temperature.